The Influence of the Pocket Book (BUSAKMIL) on the Consumption of Blood Supplement Tablets and Consumption Patterns of Anemic Pregnant Women at the Harapan Baru Community Health Center in 2023 - Rusniwati Darwis; Ratnawati; Riska Mayang Saputri G (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of BUSAKMIL on the consumption of blood supplement tablets and consumption patterns of anemic pregnant women in the Harapan Baru Community Health Center working area. The method uses a Quasi Experiment with a One Group Pretest-Posttest design and a sample of 29 respondents. The results of the study showed that there was an influence of the pocketbook (BUSAKMIL) on the consumption of blood supplement tablets by anemic pregnant women at the Harapan Baru Community Health Center in 2023 (p=0.000) and there was no influence of the pocketbook (BUSAKMIL) on protein and carbohydrate consumption patterns (p=0.109; p =0.0161) and there is an influence of the pocketbook (BUSAKMIL) on energy and fat consumption patterns (p=0.021; p=0.028) of anemic pregnant women at Harapan Baru Community Health Center.